2018
DOI: 10.1080/10942912.2018.1466321
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of aflatoxin B1 in peanut meal by electron beam irradiation

Abstract: The effects and safety of electron beam irradiation (EBI) treatment on the detoxification of aflatoxin B 1 (AFB 1) in the peanut meal were evaluated in this article. The AFB 1 degradation was predominantly affected by both initial AFB 1 and water concentrations. The degradation of AFB 1 in the selected concentrations (0.5-5 ppm) was proven to follow pseudo firstorder reaction kinetics (R 2 > 0.95). The AFB 1 degradation was faster when the initial concentration was 5 ppm and the moisture content was 21.47%, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…According to several studies summarized in Table 3, EBI has been confirmed to be an effective method for degrading aflatoxin, possessing the advantages of time saving, high efficiency, low equipment cost and dose control (Liu et al, 2018). Hashemi et al (2020) found that aflatoxin degradation efficiency increased with the increase of irradiation dose, and EBI dose of 7 kGy could reduce 77.17% AFB 1 in pistachio kernels.…”
Section: Principle and Applicationsmentioning
confidence: 99%
“…According to several studies summarized in Table 3, EBI has been confirmed to be an effective method for degrading aflatoxin, possessing the advantages of time saving, high efficiency, low equipment cost and dose control (Liu et al, 2018). Hashemi et al (2020) found that aflatoxin degradation efficiency increased with the increase of irradiation dose, and EBI dose of 7 kGy could reduce 77.17% AFB 1 in pistachio kernels.…”
Section: Principle and Applicationsmentioning
confidence: 99%
“…[22] found that EBI at doses of 10 and 5 kGy decreased the content of AFB1 in Brazilnuts by 65.7 and 53.3%, respectively, whereas γ irradiation at same doses led to reduction in AFB1 by 84.2 and 70.6%, respectively. Liu et al [23] used EBI dose of 300 kGy for reduction of AFB1 by 70%. As the selected dose was ten times of the maximum permissible dosage allowed by FDA, so this method is not highly efficient and preferable in AFB1 degradation in peanut meal.…”
Section: Irradiationmentioning
confidence: 99%
“…The presence of water in the sample matrix leads to the occurrence of a higher number of radicals produced by the EB radiation, enhancing the degradation of mycotoxins. It has been shown in the work of Liu and Lu [ 95 ] that the degradation of aflatoxin B1 in peanut meals was significantly higher for the moisture content of 21%, than for 14 and 9%. Another important factor is the type of a solvent.…”
Section: Electron Beam (Eb) Radiationmentioning
confidence: 99%